Bio‐based Poly(hydroxy urethane)s: Synthesis and Pre/Post‐Functionalization. Issue 11 (29th April 2021) - Mhd. Haniffa, Mhd. Abd. Cader; Munawar, Khadija; Ching, Yern Chee; Illias, Hazlee Azil; Chuah, Cheng Hock
Abstract: New and emerging demand for polyurethane (PU) continues to rise over the years. The harmful isocyanate binding agents and their integrated PU products are at the height of environmental concerns, in particular PU (macro and micro) pollution and their degradation problems. Non‐isocyanate poly(hydroxy urethane)s (NIPUs) are sustainable and green alternatives to conventional PUs. Since the introduction of NIPU in 1957, the market value of NIPU and its hybridized materials has increased exponentially in 2019 and is expected to continue to rise in the coming years. The secondary hydroxyl groups of these NIPU′s urethane moiety have revolutionized them by allowing for adequate pre/post functionalization. This minireview highlights different strategies and advances in pre/post‐functionalization used in biobased NIPU. We have performed a comprehensive evaluation of the development of new ideas in this field to achieve more efficient synthetic biobased hybridized NIPU processes through selective and kinetic understanding. Abstract : This minireview highlights pre‐ and post‐functionalization for the polyhydroxyurethane formed by bio‐based cyclic carbonates with diamine via aminolysis, and provides a perspective on their reaction mechanism, properties and future directions.